Traditional Leadership Meets Islamic Constitutionalism: The Status of Tungku Tigo Sajarangan in Nagari Administration - Zarista, Hasbi Azhari; pertiwi, dian; Raus, Afrian; Aris, Sarmen (UIN Mahmud Yunus Batusangkar, 2025)
The purpose of this research is to find out the position of the Tigo Sarangangan stove in the nagari government system according to constitutional law and the perspective of Islamic constitutional law. The type of research applied in this research is normative legal research with a qualitative approach, which is generally known as library research. Normative legal research is a scientific research process that aims to find the truth based on scientific logic and normative aspects. The data source used is a secondary data source. Sourced from books, articles, rules, websites. The data collection technique used is by browsing materials from books, articles, websites related to research. The data analysis technique used in this research is descriptive technique. Based on the results of research conducted by the author, it can be concluded that the Tigo Sarangan stove consists of Niniak Mamak, Alim Ulama and Cadiak Pandai. In the nagari government system, the Tigo Sarangan stove has a position as a member of the nagari customary density institution (KAN), whose elements are from the niniak mamak, the nagari ulama council institution whose elements are from the ulama and the nagari government and the nagari deliberative body whose elements are from the cadiak clever. These three institutions work together and coordinate with each other in building a nagari. In Islamic constitutional law, the Tigo Sarangan furnace can be thought of as an ahlul halli wal aqdi institution, which means a deliberative institution. In carrying out their duties, these institutions both prioritize the principles of deliberation and the general principles of Allah SWT's law in carrying out their powers and duties and conveying the aspirations of the community in government.